2008
DOI: 10.1111/j.1540-6210.2007.00859.x
|View full text |Cite
|
Sign up to set email alerts
|

Performance, Accountability, and the Debate over Rules

Abstract: Does compliance with rules ensure better program performance and accountability? Since the 1980s, many scholars have answered no to this question, arguing that as managers attempt to comply with a growing thicket of rules, they often lose sight of the performance of their agencies and programs. Even the defenders of a rules‐based approach have tended to view it as a necessary, though inconvenient, means of ensuring that democratic values and public rights are protected in the functioning of government. But doe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
5

Year Published

2010
2010
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(21 citation statements)
references
References 13 publications
0
16
0
5
Order By: Relevance
“…Third, attention was given to institutional contexts, including legislatures (Kellough and Selden 2003; Ni and Bretschneider 2007; Bourdeaux and Chikoto 2008). At the same time, it was suggested that NPM should focus more on politics (Riccucci and Thompson 2008), law (Kassel 2008), and culture (Haruna 2003). While emphasizing efficiency and effectiveness, NPM was found to be less efficient and effective in its implementation (Leland and Smirnova 2009; Lenkowsky and Perry 2000; Moynihan 2006; Thompson 2000), and the inconsistency between the theory and practice was highlighted (Van Slyke 2003; Williams 2000).…”
Section: Qualitative Observations About the Past Decade: Three Importmentioning
confidence: 99%
“…Third, attention was given to institutional contexts, including legislatures (Kellough and Selden 2003; Ni and Bretschneider 2007; Bourdeaux and Chikoto 2008). At the same time, it was suggested that NPM should focus more on politics (Riccucci and Thompson 2008), law (Kassel 2008), and culture (Haruna 2003). While emphasizing efficiency and effectiveness, NPM was found to be less efficient and effective in its implementation (Leland and Smirnova 2009; Lenkowsky and Perry 2000; Moynihan 2006; Thompson 2000), and the inconsistency between the theory and practice was highlighted (Van Slyke 2003; Williams 2000).…”
Section: Qualitative Observations About the Past Decade: Three Importmentioning
confidence: 99%
“…Raadschelders and Lee observe, for example, that the success of NPM is based on the administrative capacity of government (see Brown and Potoski ; Yang, Hsieh, and Li ), that it has not paid adequate attention to politics, law and culture (Haruna ; Kassel ; Riccucci and Thompson ), that it is less efficient and effective than expected (Leland and Smirnova ; Lenkowsky and Perry ; Moynihan ; Thompson ), and that there remains a disconnect between theory and practice (Van Slyke ; Williams ). Some scholars maintain that legislative and judicial constraints have been overlooked (Reed and Meyer ) and that NPM has eroded accountability to citizens and civil society (Eikenberry and Kluver ; Kelly ; Romzek and Johnston ).…”
mentioning
confidence: 99%
“…More broadly, the association between mission‐extrinsic public values and agency performance has been the focus of much empirical research for decades (Kassel ). For example, some scholars have found that citizen participation contributes to improving government decisions and government‐citizen relationships (Yang and Pandey ), whereas others have found no such positive effect of citizen participation under certain conditions (Irvin and Stansbury ).…”
Section: Mission‐extrinsic Public Valuesmentioning
confidence: 99%